Low-expansion microcrystalline glass as well as preparation method and application thereof

By adopting specific chemical composition and controlled crystallization preparation methods, low-expanded crystallized glass with β-quartz solid solution as the main crystal phase was prepared, which solved the problem of high thermal expansion coefficient of existing crystallized glasses and achieved high-precision extreme ultraviolet lithography materials.

CN119859023AActive Publication Date: 2025-04-22LUMISING SPECIAL GLASS TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510171393.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-22
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

The existing microcrystalline glass has a high thermal expansion coefficient and cannot meet the high precision requirements of extreme ultraviolet lithography.

Method used

Low-expanded crystallized glass with specific chemical composition, including oxides such as SiO2, Al2O3, Li2O, MgO, ZnO, P2O5, TiO2, ZrO2, Gd2O3, SnO2 and CaF2, is used to form a low-expanded transparent crystallized glass with β-quartz solid solution as the main crystal phase through a strict controlled crystallization preparation method.

Benefits of technology

It achieves ultra-low thermal expansion coefficient, excellent optical and mechanical properties, and can meet the strict requirements of extreme ultraviolet lithography on high-precision optical component materials, providing key material support for the further development of extreme ultraviolet lithography technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005274146610000081
    Figure BDA0005274146610000081
  • Figure BDA0005274146610000091
    Figure BDA0005274146610000091
  • Figure FDA0005274146600000011
    Figure FDA0005274146600000011
Patent Text Reader

Abstract

The invention discloses low-expansion microcrystalline glass as well as a preparation method and application thereof. The low-expansion microcrystalline glass is prepared from the following components in percentage by weight: 56 to 67 percent of SiO2, 18 to 27 percent of Al2O3, 3.1 to 7.0 percent of Li2O, 0.1 to 0.5 percent of MgO, 0.1 to 0.9 percent of ZnO, 1.0 to 2.9 percent of P2O5, 1.0 to 2.9 percent of TiO2, 1.0 to 2.9 percent of ZrO2, 0.5 to 4 percent of Gd2O3, 0.6 to 1.5 percent of SnO2 and 0.1 to 0.4 percent of CaF2. The low-expansion microcrystalline glass prepared by the method has excellent performances such as low thermal expansion coefficient, good visible light transmittance and the like, and can be applied to the field of extreme ultraviolet lithography.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of special glass materials, and in particular to a low-expansion microcrystalline glass and a preparation method thereof. Background Art

[0002] Low expansion glass-ceramics not only has ultra-low thermal expansion performance, but also has good light transmittance, and can obtain transparent and colorless glass-ceramics. Therefore, it is widely used in reflectors of large astronomical telescopes, high-temperature observation windows, laser gyroscopes, etc. Due to its extremely low thermal expansion coefficient, high thermal shock resistance, excellent chemical stability and mechanical properties, it plays a very important role in civil and military fields.

[0003] Extreme ultraviolet lithography (EUVL) is an advanced lithography technology. It is a microelectronic lithography technology that uses extreme ultraviolet rays with a wavelength of 10nm-14nm as the exposure light source. It is an advanced lithography technology for manufacturing microprocessor units (MPU) and dynamic random access memory (DRAM) chips. It has important applications in semiconductor manufacturing and other fields. With the continuous development of semiconductor technology, the requirements for chip manufacturing accuracy and integration are getting higher and higher. Due to the advantages of high precision and high resolution, extreme ultraviolet lithography plays a key role in manufacturing smaller and more complex chip structures, making extreme ultraviolet lithography gradually become mainstream. In the future, with the rapid development of 5G, artificial intelligence, the Internet of Things and other fields, the demand for high-performance chips will further promote the development of extreme ultraviolet lithography.

[0004] In the EUV lithography system, optical components need to have characteristics such as high precision, high stability and low expansion coefficient to ensure the accuracy and quality of lithography. Low expansion glass for EUV lithography is a special glass material designed specifically for EUV lithography technology. It is a key material in the process of manufacturing high-precision and high-integration semiconductor chips. Low expansion glass for EUV lithography is a special glass with an extremely low thermal expansion coefficient. It is mainly used in the semiconductor manufacturing field to manufacture core key components of EUV lithography machines, such as mirrors and lenses. As a key material in EUV lithography machines, the stability and reliability of the performance of low expansion glass for EUV lithography have an important impact on the lithography effect. Therefore, the demand for low expansion glass in the semiconductor manufacturing industry will continue to grow. Low expansion glass for EUV lithography requires the following special requirements:

[0005] (1) Low thermal expansion coefficient: Low expansion glass for EUV lithography has an extremely low thermal expansion coefficient and can maintain stable size and shape in high temperature and large temperature change environments; its low thermal expansion characteristics ensure the stability and precision of optical components during the lithography process, thereby improving the resolution and yield of lithography.

[0006] (2) High optical performance: Low expansion glass for EUV lithography has excellent optical properties, including high transmittance, low scattering and low absorption, ensuring high imaging quality during EUV lithography.

[0007] (3) Good mechanical properties: Low expansion glass for EUV lithography has high mechanical strength and hardness and can withstand the high pressure and high temperature during the lithography process.

[0008] (4) High purity: The impurity content in low-expansion glass materials used in EUV lithography is required to be extremely low to reduce the absorption and scattering of EUV light and improve lithography efficiency.

[0009] Traditional microcrystalline glass has been widely studied for the manufacture of optical components due to its good optical properties and chemical stability. However, it is difficult for traditional microcrystalline glass to meet the increasingly high technical requirements of extreme ultraviolet lithography in terms of thermal expansion performance. At present, the ultra-low expansion glass materials used in lithography systems are mainly divided into two categories: one is amorphous ultra-low expansion glass, and the other is microcrystalline ultra-low expansion transparent microcrystalline glass. However, amorphous ultra-low expansion glass is difficult to meet the requirements of extreme ultraviolet lithography in terms of optical processing. The research on transparent microcrystalline glass has always been a hot topic in the field of special glass research. However, so far, the successful development of ultra-low expansion microcrystalline glass is very rare. The difficulty lies in the selection of components, the control of crystallization temperature and crystallization time, so that the glass can precipitate uniform and fine nano-sized grains during heat treatment.

[0010] Therefore, developing an ultra-low expansion glass-ceramic with a low expansion coefficient suitable for extreme ultraviolet lithography applications has important practical significance and application value. Summary of the invention

[0011] In order to overcome the problems existing in the prior art, the purpose of the present invention is to provide a low-expansion microcrystalline glass and a preparation method thereof, so as to solve the problem that the existing microcrystalline glass has a high thermal expansion coefficient and cannot meet the high-precision requirements of extreme ultraviolet lithography.

[0012] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0013] A low expansion glass-ceramic, characterized in that it is prepared by including the following oxides in weight percentage (wt.%):

[0014] SiO2 56-67%

[0015] Al2O3 18-27%

[0016] Li2O 3.1-7%

[0017] MgO 0.1-0.5%

[0018] ZnO 0.1-0.9%

[0019] P2O5 1.0-2.9%

[0020] TiO2 1.0-2.9%

[0021] ZrO2 1.0-2.9%

[0022] Gd2O3 0.5-4%

[0023] SnO2 0.6-1.5%

[0024] CaF2 0.1-0.4%.

[0025] Preferably, the following oxides are prepared in accordance with mass percentage (wt.%):

[0026] SiO2 58-66%

[0027] Al2O3 20-25%

[0028] Li2O 3.5-6%

[0029] MgO 0.1-0.5%

[0030] ZnO 0.1-0.9%

[0031] P2O5 1.0-2.9%

[0032] TiO2 1.0-2.9%

[0033] ZrO2 1.0-2.9%

[0034] Gd2O3 0.5-4%

[0035] SnO2 0.6-1.5%

[0036] CaF2 0.1-0.4%.

[0037] The low expansion glass-ceramics of the present invention is a low expansion transparent glass-ceramics with β-quartz solid solution as the main crystal phase, which is prepared by strictly controlled crystallization of glass with Li2O, Al2O3 and SiO2 as the main components.

[0038] SiO2 is the main component of the glass skeleton structure and plays a major role in the glass skeleton. The weight percentage (wt.%) of SiO2 is 56-67. When the SiO2 content is lower than 55wt.%, it is difficult to obtain a low-expansion transparent microcrystalline glass with β-quartz solid solution as the main crystal phase, and it will also reduce the chemical resistance and mechanical strength of the microcrystalline glass; when the SiO2 content is higher than 67wt.%, the high-temperature viscosity of the glass will increase, causing the glass melting temperature to be too high.

[0039] Al2O3 is an intermediate oxide of glass. 3+ There are two coordination states, namely, located in tetrahedron or octahedron. When there is enough oxygen in the glass, aluminum oxide tetrahedron [AlO4] is formed, forming a continuous network with silicon oxide tetrahedron. When there is insufficient oxygen in the glass, aluminum oxide octahedron [AlO6] is formed, which is an external body of the network and is located in the cavities of the silicon oxide structure network. The weight percentage (wt.%) of Al2O3 is 18-27. The Al2O3 content less than 18wt.% will reduce the chemical stability and thermal stability of the glass; the Al2O3 content greater than 27wt.% will significantly increase the melting temperature of the glass, and at the same time increase the nucleation and crystallization temperature of the microcrystalline glass, making the grain size coarse and uneven.

[0040] Li2O is a glassy network oxide. + It can be filled in the cavities of the glass structure to maintain electrical neutrality. The weight percentage (wt.%) of Li2O is 3.1-7.0. When the content of Li2O is lower than 3.1%, the melting viscosity of the glass will increase; when the content of Li2O is higher than 7.0%, the expansion coefficient of the microcrystalline glass will increase.

[0041] MgO is a network-external oxide of the glass structure, which can improve the mechanical properties of microcrystalline glass and reduce the crystallization rate, thereby reducing the glass melting temperature and molding temperature, slowing down the hardening rate of the glass and improving the molding performance. The weight percentage (wt.%) of MgO is 0.1-0.5. When the content of MgO is less than 0.1%, the mechanical properties of microcrystalline glass will be reduced; when the content of MgO is greater than 0.5%, crystalline phases such as cordierite and spinel will precipitate, affecting the performance of microcrystalline glass products.

[0042] As a flux, ZnO can reduce the high-temperature viscosity of glass, thereby reducing the melting temperature of glass, and can also reduce the thermal expansion coefficient of microcrystalline glass. The weight percentage (wt.%) of ZnO is 0.1-0.9. If the content of ZnO is lower than 0.1%, it will not reduce the high-temperature viscosity of glass; if the content of ZnO is higher than 0.9%, crystalline phases such as cordierite and spinel will be precipitated during the crystallization of glass, affecting the performance of microcrystalline glass products.

[0043] P2O5, TiO2, and ZrO2 can affect the phase separation and crystal phase transition process of glass and are good nucleus inducers. Among them, ZrO2 can delay the transformation of β-quartz solid solution to β-spodumene solid solution and increase the transparency of microcrystalline glass. ZrO2 has only one six-coordinated state in glass. It is incompatible with the silicon-oxygen network and only exists in the cavities outside the network, making its structure compact. The weight percentage (wt.%) of ZrO2 is 1.0-2.9. When the content of ZrO2 is less than 1.0%, the crystallization temperature of the glass will be increased; when the content of ZrO2 exceeds 2.9%, it is easy to produce insoluble substances, resulting in devitrification of microcrystalline glass.

[0044] The weight percentage (wt.%) of P2O5 is 1.0-2.9. When the content of P2O5 is lower than 1.0%, the β-quartz solid solution grains will grow too large to cause fogging, or the degree of crystallization will be insufficient, resulting in too high thermal expansion coefficient of microcrystalline glass products; when the content of P2O5 is greater than 2.9%, the volatilization will increase, making the molten glass stripes serious. P2O5 is introduced by aluminum metaphosphate Al(PO3)3. The addition of P2O5 can reduce the melting temperature of ZrO2 and promote the melting of ZrO2, which is conducive to phase separation and thus forms a three-dimensional interconnected structure.

[0045] TiO2 has a relatively high solubility in glass, is easier to melt, and has a higher crystallization rate than ZrO2. TiO2 is an intermediate oxide in glass. 4+ There are two coordination states in the glass structure, [TiO4] and [TiO6]. At high temperature, Ti 4+ It exists in a four-coordinated form and participates in the silicon-oxygen network structure. At low temperatures, TiO2 will separate from the silicon-oxygen network together with oxides such as MgO and ZnO to form a crystal nucleus, which promotes the crystallization of the glass. The weight percentage (wt.%) of TiO2 is 1.0-2.9. If the content of TiO2 is less than 1.0%, the crystal grains of the microcrystalline glass will grow too large and the thermal expansion coefficient will increase; if the content of TiO2 is greater than 2.9%, the microcrystalline glass will appear yellow and the transmittance of the microcrystalline glass will be reduced.

[0046] Gd2O3 can reduce the crystallization temperature of glass-ceramics, shorten the crystallization time, improve the mechanical strength of glass-ceramics, and make the grain size uniform after crystallization. The weight percentage (wt.%) of Gd2O3 is 0.5-4. If the content of Gd2O3 is less than 0.5%, the crystallization time will be increased; if the content of Gd2O3 is greater than 4.0%, the grains of glass-ceramics will grow too large and the thermal expansion coefficient will increase.

[0047] SnO2 is mainly used as a glass clarifier to clarify bubbles in glass melt, and also as a variable ion to enhance the crystallization effect of glass. The weight percentage (wt.%) of SnO2 is 0.6-1.5%. If the content of SnO2 is less than 0.6%, the clarification effect of glass melt cannot be achieved; if the content of SnO2 is greater than 1.5%, the thermal expansion coefficient of microcrystalline glass will increase.

[0048] CaF2 can lower the liquidus temperature of glass and improve the glass-forming ability. The weight percentage (wt.%) of CaF2 is 0.1-0.4. When the CaF2 content is less than 0.1%, the chemical resistance of the microcrystalline glass will be reduced; when the CaF2 content is greater than 0.4%, the thermal expansion coefficient of the microcrystalline glass will be increased.

[0049] The low-expansion microcrystalline glass of the present invention does not contain any of B2O3, Na2O, K2O, etc., and does not contain B2O3 to reduce the occurrence of phase separation of the glass; at the same time, alkali metal oxides Na2O and K2O are not used to reduce the opacity and poor light transmittance of crystallized microcrystalline glass products.

[0050] The low-expansion microcrystalline glass of the present invention does not contain any metal oxides harmful to the environment, such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO, V2O5, etc. Even if it contains very small amounts, they are introduced from other glass raw materials.

[0051] The present invention also provides a method for preparing the low-expansion glass-ceramics, comprising the following steps:

[0052] (1) Raw material preparation: weigh the raw materials according to the above chemical composition and raw material requirements, add 5% by weight of pure water to the weighed raw materials and mix them evenly to obtain a mixed raw material;

[0053] (2) Melting and forming: the mixed raw materials are placed in a glass melting furnace and smelted at a high temperature of 1550-1650° C. for 6-10 hours to fully melt the raw materials and mix them evenly to form a uniform glass liquid; during the glass melting process, a stirring device is used to stir the glass liquid at a stirring speed of 20-40 revolutions per minute to fully discharge bubbles and impurities in the glass liquid;

[0054] (3) Clarification and homogenization: The stirred molten glass is passed through a platinum channel for clarification and homogenization to obtain clarified molten glass;

[0055] (4) Forming the blank: Casting the clarified glass liquid into a preheated heat-resistant steel mold to form a glass blank of the desired shape;

[0056] (5) Annealing treatment: placing the glass body in an annealing furnace, heating it to 550-600°C at a rate of 1-3°C / min, keeping it at that temperature for 2-4 hours, then cooling it to below 300°C at a rate of 0.5-1.5°C / hour, and cooling it to room temperature;

[0057] (6) Nucleation and crystallization: The glass blank is then placed in a high-precision annealing furnace, and the sample is heated from room temperature to 630-690°C at a heating rate of 1-3°C / hour, and kept at this temperature for 3-5 hours for nucleation. The temperature is then further raised to 750-810°C and kept at this temperature for 2-6 hours for crystallization. The nucleation and crystallization process is carried out in a reducing atmosphere, and the reducing atmosphere is obtained by placing 3-5% of the sample weight of carbon powder next to the sample. After the crystallization treatment, the temperature is lowered to room temperature at a cooling rate of 0.1-0.5°C / min, and low expansion microcrystalline glass is obtained after processing.

[0058] The low-expansion glass-ceramics of the present invention is an ultra-low-expansion transparent glass-ceramics of a Li2O-Al2O3-SiO2 system with a nano-β-quartz solid solution as the main crystal phase. The grain size of the precipitated β-quartz solid solution phase is 30-60nm, which is one-tenth of the visible light wavelength range (380nm-780nm), and the refractive index of the crystal phase is close to that of glass. Therefore, the light transmittance is high in the visible light and infrared light range. At the same time, it has ultra-low expansion performance close to zero, excellent three-dimensional overall uniformity, good processing performance, can be polished to extremely high precision, good film-coating performance, excellent chemical resistance and stability, etc.

[0059] The present invention also provides an application of the low-expansion microcrystalline glass prepared according to the above preparation method in optical precision components, astronomy, extreme ultraviolet lithography or microlithography, such as standard parts for precision measurement technology, as mechanical precision parts of ring laser gyroscopes, spiral springs for the watchmaking industry, mask holders, wafer stages or reference plates in extreme ultraviolet lithography or as optical components in extreme ultraviolet lithography, used as reflectors and prisms in extreme ultraviolet lithography, and in particular as substrates for extreme ultraviolet mask blanks or extreme ultraviolet reflectors.

[0060] Compared with the prior art, the low expansion glass-ceramics provided by the present invention has the following significant advantages:

[0061] (1) The low-expansion glass-ceramics of the present invention does not contain any oxides such as B2O3, Na2O, K2O, etc. that are harmful to the photolithography environment and unfavorable to the extreme ultraviolet photolithography coating process, and has excellent electrical insulation and a stable dielectric constant;

[0062] (2) The thermal expansion coefficient of the low expansion glass-ceramics of the present invention is extremely low, and its thermal expansion coefficient in the temperature range of 0 to 50°C is (0±1.2)×10 -7 / ℃; has good high temperature resistance and thermal shock resistance;

[0063] (3) The low expansion glass-ceramics of the present invention has a single ultrafine grain structure. After controlled crystallization, β-quartz solid solution crystals are precipitated in the glass as a whole, and the grain size is 30-60 nm. Therefore, in addition to a small amount of light absorption, the transmittance of the 5 mm thick low expansion glass-ceramics is greater than 85%;

[0064] (4) The low expansion glass-ceramics of the present invention has an ultrafine microcrystalline structure and a uniform and dense texture, and therefore has excellent mechanical properties, a bending strength greater than 120 MPa, and good wear resistance.

[0065] The low-expansion glass-ceramics of the present invention optimizes the chemical composition and introduces appropriate amounts of oxides such as Gd2O3 and SnO2, thereby effectively reducing the thermal expansion coefficient of the glass while ensuring the good optical properties and chemical stability of the glass. High-quality low-expansion glass-ceramics can be prepared, and the glass also performs well in terms of optical transmittance, chemical stability and mechanical strength. The low-expansion glass-ceramics can well meet the strict requirements of extreme ultraviolet lithography for high-precision optical element materials, providing key material support for the further development of extreme ultraviolet lithography technology, and having broad application prospects and significant economic benefits. DETAILED DESCRIPTION

[0066] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention are described in further detail below.

[0067] The present invention is further described in detail below in conjunction with specific embodiments, but is not intended to be limiting of the present invention. The parameters, measurement methods and instruments for a low expansion glass-ceramic of the present invention are as follows:

[0068] (1) The thermal expansion coefficient of glass-ceramics is measured by a horizontal dilatometer and expressed as the average linear expansion coefficient using the method specified in GB / T 7962.16-2010;

[0069] (2) The transmittance of the glass-ceramics is tested according to the method specified in GB / T 7962.12-2010. The transmittance of the 5 mm sample of the glass-ceramics of the present invention is the transmittance at 530 nm.

[0070] (3) The bending strength of glass-ceramics shall be tested in accordance with the method specified in GB / T 6569-2006.

[0071] The following Table 1 shows the performance of the embodiments of the present invention and the tests.

[0072] Table 1 Chemical composition (wt.%) and properties of glass-ceramics of the examples

[0073]

[0074]

[0075] The following are the raw materials used in the examples and their requirements:

[0076] Quartz sand (high purity, 150 μm sieve content of less than 1%, 45 μm sieve content of less than 30%, Fe2O3 content less than 0.01 wt.%), alumina (analytical grade, average particle size 50 μm), lithium carbonate (analytical grade, 400 μm sieve content of less than 10%, 63 μm sieve content of less than 10%), basic magnesium carbonate (analytical grade), zinc oxide (analytical grade), aluminum metaphosphate (analytical grade), titanium oxide (analytical grade), zirconium oxide (analytical grade), gadolinium oxide (analytical grade), tin oxide (analytical grade, average particle size 60 μm sieve content of less than 1%), calcium fluoride (analytical grade).

[0077] Example 1

[0078] The raw materials are selected according to the components of Example 1 in Table 1, and the Fe content in the raw materials is strictly controlled so that the ingredients meet the glass chemical composition of Table 1. The weighed raw materials are added with 5% of the total weight of pure water and mixed evenly to obtain a mixed raw material. The mixed raw material is then placed in a glass melting furnace and smelted at a high temperature of 1600° C. for 8 hours to fully melt the raw materials and mix evenly to form a uniform glass liquid. During the glass melting process, a stirring device is used to stir the glass liquid at a stirring speed of 30 rpm to fully discharge bubbles and impurities in the glass liquid. The stirred glass liquid is then passed through a platinum channel for clarification and homogenization to obtain a clarified glass liquid. The clarified glass liquid is cast in a preheated heat-resistant steel mold to form the desired shaped glass body; placing the glass body in an annealing furnace, heating the sample from room temperature to 670°C at a heating rate of 2°C / hour, keeping it warm for 3 hours, then cooling it down to below 300°C at a rate of 1.0°C / hour, taking it out and cooling it to room temperature; then placing the glass body in a high-precision annealing furnace, heating the sample from room temperature to 670°C at a heating rate of 2°C / hour, keeping it warm for 4 hours for nucleation, then continuing to heat it up to 780°C and keeping it warm for 4 hours for crystallization, the nucleation and crystallization process is carried out in a reducing atmosphere, the reducing atmosphere is obtained by placing 4% of the sample weight of carbon powder next to the sample, after the crystallization treatment, the temperature is cooled to room temperature at a cooling rate of 0.3°C / min, and low expansion microcrystalline glass is obtained after processing, and its test properties are shown in Table 1.

[0079] Example 2

[0080] The raw materials are selected according to the components of Example 2 in Table 1, and the Fe content in the raw materials is strictly controlled so that the ingredients meet the glass chemical composition of Table 1. The weighed raw materials are added with 5% of the total weight of pure water and mixed evenly to obtain a mixed raw material. The mixed raw material is then placed in a glass melting furnace and smelted at a high temperature of 1650° C. for 6 hours to fully melt the raw materials and mix evenly to form a uniform glass liquid. During the glass melting process, a stirring device is used to stir the glass liquid at a stirring speed of 40 rpm to fully discharge bubbles and impurities in the glass liquid. The stirred glass liquid is then passed through a platinum channel for clarification and homogenization to obtain a clarified glass liquid. The clarified glass liquid is cast into a preheated heat-resistant steel mold to form the desired shaped glass body; placing the glass body in an annealing furnace, heating the sample from room temperature to 630°C at a heating rate of 1°C / hour, keeping it warm for 5 hours for nucleation, and then continuing to heat the sample to 750°C and keeping it warm for 6 hours for crystallization, wherein the nucleation and crystallization process are carried out in a reducing atmosphere, wherein the reducing atmosphere is obtained by placing 3% of the sample weight of carbon powder next to the sample, and after the crystallization treatment, the temperature is lowered to room temperature at a cooling rate of 0.1°C / min, and low expansion microcrystalline glass is obtained after processing, and its test properties are shown in Table 1.

[0081] Example 3

[0082] The raw materials are selected according to the components of Example 3 in Table 1, and the Fe content in the raw materials is strictly controlled so that the ingredients meet the glass chemical composition of Table 1. The weighed raw materials are added with 5% of the total weight of pure water and mixed evenly to obtain a mixed raw material. The mixed raw material is then placed in a glass melting furnace and smelted at a high temperature of 1550° C. for 10 hours to fully melt the raw materials and mix evenly to form a uniform glass liquid. During the glass melting process, a stirring device is used to stir the glass liquid at a stirring speed of 20 rpm to fully discharge bubbles and impurities in the glass liquid. The stirred glass liquid is then passed through a platinum channel for clarification and homogenization to obtain a clarified glass liquid. The clarified glass liquid is cast into a preheated heat-resistant steel mold to form the desired shaped glass body; placing the glass body in an annealing furnace, heating the sample from room temperature to 690°C at a heating rate of 3°C / hour, keeping it warm for 3 hours for nucleation, and then continuing to heat the sample to 810°C and keeping it warm for 2 hours for crystallization, wherein the nucleation and crystallization process are carried out in a reducing atmosphere, wherein the reducing atmosphere is obtained by placing 5% of the sample weight of carbon powder next to the sample, and after the crystallization treatment, the sample is cooled to room temperature at a cooling rate of 0.5°C / min, and a low expansion microcrystalline glass is obtained after processing, and its test properties are shown in Table 1.

[0083] Example 4

[0084] The raw materials are selected according to the components of Example 4 in Table 1, and the Fe content in the raw materials is strictly controlled so that the ingredients meet the glass chemical composition of Table 1. The same process system and test conditions as Example 1 are used, and the basic properties of the samples are shown in Table 1.

[0085] Example 5

[0086] The raw materials are selected according to the components of Example 5 in Table 1, and the Fe content in the raw materials is strictly controlled so that the ingredients meet the glass chemical composition of Table 1. The same melting process system and test conditions as in Example 1 are used. The basic properties of the samples are shown in Table 1.

[0087] From the data obtained in the examples, it can be seen that the low-expansion microcrystalline glass of the present invention does not contain any metal oxides or heavy metal oxides that are harmful to the environment, such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO, V2O5, etc., and is green and environmentally friendly; and by introducing an appropriate amount of oxides such as Gd2O3 and SnO2, the thermal expansion coefficient of the glass is effectively reduced, while ensuring the good optical properties and chemical stability of the glass, and high-quality low-expansion microcrystalline glass can be prepared, and it also performs well in terms of optical transmittance, chemical stability and mechanical strength, and can well meet the strict requirements of extreme ultraviolet lithography for high-precision optical component materials, and provides key material support for the further development of extreme ultraviolet lithography technology, and has broad application prospects and significant economic benefits.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make any modification or equivalent substitution, improvement, etc. to the present invention within the essence and protection scope of the present invention, and such modification or equivalent substitution is also deemed to fall within the protection scope of the present invention.

Claims

1. A low expansion glass-ceramic, characterized in that: The invention comprises the following oxides prepared according to mass percentage (wt.%):

2. A low expansion glass-ceramic according to claim 1, characterized in that: Preferably, the following oxides are prepared in accordance with mass percentage (wt.%):

3. A low expansion glass-ceramic according to claim 1 or 2, characterized in that: The low expansion glass-ceramics does not contain any of B2O3, Na2O, K2O and the like.

4. A low expansion glass-ceramic according to claims 1 to 3, characterized in that: It does not contain substantially any metal oxides harmful to the environment, such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO, V2O5, etc.

5. The low expansion glass-ceramic according to claims 1 to 4, characterized in that: The thermal expansion coefficient of the ultra-low expansion glass-ceramics in the temperature range of 0-50°C is (0±1.2)×10 -7 / ℃.

6. The low expansion glass-ceramics according to claims 1 to 5, characterized in that: After the low expansion glass-ceramics is controlled crystallized, the grain size is 30-60 nm, and the transmittance of the 5 mm thick low expansion glass-ceramics is greater than 85%.

7. The low expansion glass-ceramics according to claims 1 to 6, characterized in that: The low expansion glass-ceramics has a bending strength greater than 120 MPa and good wear resistance.

8. A method for preparing low expansion glass-ceramics according to claims 1 to 7, characterized in that: The following steps are involved: (1) Raw material preparation: weigh the raw materials according to the above chemical composition and raw material requirements, add 5% by weight of pure water to the weighed raw materials and mix them evenly to obtain a mixed raw material; (2) Melting and forming: the mixed raw materials are placed in a glass melting furnace and smelted at a high temperature of 1550-1650° C. for 6-10 hours to fully melt the raw materials and mix them evenly to form a uniform glass liquid; during the glass melting process, a stirring device is used to stir the glass liquid at a stirring speed of 20-40 revolutions per minute to fully discharge bubbles and impurities in the glass liquid; (3) Clarification and homogenization: The stirred molten glass is passed through a platinum channel for clarification and homogenization to obtain clarified molten glass; (4) Forming the blank: Casting the clarified glass liquid into a preheated heat-resistant steel mold to form a glass blank of the desired shape; (5) Annealing treatment: placing the glass body in an annealing furnace, heating it to 550-600°C at a rate of 1-3°C / min, keeping it at that temperature for 2-4 hours, then cooling it to below 300°C at a rate of 0.5-1.5°C / hour, and cooling it to room temperature; (6) Nucleation and crystallization: The glass blank is then placed in a high-precision annealing furnace, and the sample is heated from room temperature to 630-690°C at a heating rate of 1-3°C / hour, and kept at that temperature for 3-5 hours for nucleation. The temperature is then further raised to 750-810°C and kept at that temperature for 2-6 hours for crystallization. The nucleation and crystallization process is carried out in a reducing atmosphere. After the crystallization treatment, the temperature is lowered to room temperature at a cooling rate of 0.1-0.5°C / min. After processing, low expansion microcrystalline glass is obtained.

9. The method for preparing low expansion glass-ceramics according to claim 8, characterized in that: The reducing atmosphere is obtained by placing carbon powder of 3-5% of the sample weight beside the sample.

10. Application of the low expansion glass-ceramics according to any one of claims 1 to 7 in optical precision components, astronomy, extreme ultraviolet lithography or microlithography, for example as mechanical precision parts of ring laser gyroscopes, mask holders, wafer stages or reference plates in extreme ultraviolet lithography or as optical components in extreme ultraviolet lithography, in particular as substrates for extreme ultraviolet mask blanks or extreme ultraviolet reflectors.

Citation Information

Patent Citations

  • Crystallized glass and method for producing crystallized glass

    CN101085699A

  • Process for production of LAS-system crystalline glass

    CN102781864A

  • Glass ceramic and glass ceramic product

    CN114671619A

  • Glass ceramic, glass ceramic product and manufacturing method thereof

    CN115636589A

  • Low-expansion-coefficient transparent microcrystalline glass and preparation method thereof

    CN116332517A